Historiography of the establishment of the tahfiz plus program at Universiti Teknologi MARA based on the ADDIE model / Najahudin Lateh, Muhamad Rahimi Osman and Ghafarullahhuddin Din - Lateh, Najahudin; Osman, Muhamad Rahimi; Din, Ghafarullahhuddin (Universiti Teknologi MARA, 2022)
The establishment of the Plus Tahfiz program to strengthen the memorization of the Qur'an at Universiti Teknologi MARA (UiTM) in 2018 is the first of its kind in Malaysian higher education institutions. However, to date there has not been any scholarly writing related to the facts or history of the establishment of this program that has been compiled or written. Therefore, this paper was produced with the objective of recording the history of this program for the reference of various parties in the future. This study is qualitative in nature with a research framework based on the ADDIE Model developed by Molenda (2003) and modified into three phases, namely needs analysis, design and development. Data were collected from official university and external documentation as well as observations based on the author's own experience who was directly involved in the proposed establishment. The data obtained were analyzed descriptively through content analysis methods with inductive and deductive processing. The results of this study obtained the historiography of the establishment of the Plus Tahfiz program in three phases according to the chronology of time for a year from October 2017 to September 2018 before being implemented throughout the campus at UiTM. This study is very beneficial to the information system of educational institutions, especially at UiTM as well as the main reference related to this program to all university administrators, tahfiz institutions, researchers and all lovers of Quranic knowledge.